Clinical and radiologic factors associated with orbital drainage in pediatric sinusitis-associated subperiosteal abscess: a four-season retrospective cohort of 112 cases - Ahmad Saberghadim; Mohammad Taher Rajabi; Amirhossein Aghajani; Pedram Afshar; Ali Ghasemi; Elham Rahmanikhah; Amin Zand; Afsaneh Malekpour; Reza Sadeghi; Shakiba Dehghani; Seyed Mohsen Rafizadeh (Journal of Ophthalmic Inflammation and Infection, 2026)
Abstract Background Pediatric sinusitis-associated orbital subperiosteal abscess (SPA) can threaten vision and sometimes prompts urgent orbital drainage, but the clinical and radiologic factors associated with this management decision remain incompletely defined. Methods This retrospective cohort study included consecutive patients younger than 18 years admitted to a tertiary referral eye hospital in Tehran, Iran, with computed tomography (CT)-confirmed orbital SPA secondary to sinusitis during four autumn-winter seasons from 2022 to 2026. SPA volume was calculated on admission CT images using an ellipsoid approximation formula. The primary outcome was orbital abscess drainage during the index hospitalization, representing the treatment performed rather than an independently adjudicated need for surgery. Group comparisons, multivariable logistic regression, sensitivity analyses, and exploratory receiver operating characteristic (ROC) analysis were performed. Results The study included 112 patients; 78 (69.6%) underwent orbital drainage and 34 (30.4%) did not. Patients who underwent drainage were older (9.10 ± 3.79 vs. 5.85 ± 3.17 years; P < .001), had larger SPA volumes (median, 1.70 vs. 0.65 cm³; P < .001), and more frequently had a superior-component location, proptosis, chemosis, and ocular motility limitation. In the primary parsimonious model, older age (adjusted odds ratio [aOR], 1.186 per year; 95% confidence interval [CI], 1.005 to 1.400; P = .044) and larger SPA volume (aOR, 3.160 per 1-cm³ increase; 95% CI, 1.562 to 6.395; P = .001) remained independently associated with drainage. Superior-component location showed a large but imprecise association (aOR, 6.702; 95% CI, 0.742 to 60.553; P = .090). The model area under the ROC curve was 0.878. An exploratory internally derived SPA-volume cutoff of 865 mm³ had apparent sensitivity of 82.1% and specificity of 73.5%. Conclusions Older age and larger CT-based SPA volume were independently associated with orbital drainage as performed in routine clinical practice. Superior-component location may also be clinically relevant, although its adjusted estimate was imprecise. The internally derived 865-mm³ cutoff is hypothesis-generating and should not be used as a stand-alone indication for drainage without external validation.